Optimal taxation under different concepts of justness - Robin Jessen; Maria Metzing; Davud Rostam-Afschar (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
A common assumption in the optimal taxation literature is that the social planner maximizes a welfarist social welfare function with weights decreasing with income. However, high transfer withdrawal rates in many countries imply very low weights for the working poor in practice. We extend the optimal taxation framework by Saez (2002) to allow for alternatives to welfarism. We calculate weights of a social planner's function as implied by the German tax and transfer system based on the concepts of welfarism, minimum absolute and minimum relative sacrifice. We find that the minimum absolute sacrifice principle is in line with social weights that decline with net income. – – Üblicherweise wird in der Optimalbesteuerungsliteratur angenommen, dass der soziale Planer eine utilitaristische soziale Wohlfahrtsfunktion maximiert, bei der die sozialen Wohlfahrtsgewichte mit dem Nettoeinkommen fallen. Auf der anderen Seite implizieren die hohen Transferentzugsraten vieler Staaten sehr niedrige Gewichte für arbeitende Geringverdiener. Wir erweitern das Optimalbesteuerungsmodell von Saez (2002), um nicht-utilitaristische Ziele des sozialen Planers abzubilden. Wir berechnen die vom deutschen Steuer- und Transfersystem implizierten Gewichte der Zielfunktion des sozialen Planers auf Grundlage der Gerechtigkeitskonzepte Utilitarismus sowie der relativen und absoluten Opfertheorie. Die absolute Opfertheorie ist im Einklang mit mit dem Nettoeinkommen fallenden sozialen Gewichten.
Keywords: D63; D60; H21; H23; I38; 330; justness; optimal taxation; income redistribution; equal sacrifice; inequality; subjective preferences